1987
DOI: 10.1111/j.1476-5381.1987.tb11212.x
|View full text |Cite
|
Sign up to set email alerts
|

BW A575C, a chemically novel agent with angiotensin converting enzyme inhibitor and β‐adrenoceptor‐blocking properties

Abstract: ) is a chemically novel agent which exhibits in a single molecule both angiotensin converting enzyme (ACE) inhibition and P-adrenoceptor-blocking properties.2 BW A575C produced a competitive blockade of heart rate responses to isoprenaline in a guinea-pig right atrial preparation (pKB 7.18 ± 0.05, cf. pindolol 8.9 ± 0.7). BW A575C inhibited a partially purified preparation of ACE obtained from rabbit lung (IC50 10.7 + 2.1 nM, cf. enalaprilat, 4.4 ± 0.8 nM).3 Intravenous administration of BW A575C (1-100 tgkg-'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…For example, carvedilol is a bioavailable alphaand beta-adrenoceptor blocking drug. BWA 575C [3,4] is a novel drug that combines the properties of angiotensin-converting enzyme inhibition with betaadrenoceptor blockade. Another approach has been to separate and examine the pharmacology of the individual stereoisomers of labetalol.…”
mentioning
confidence: 99%
“…For example, carvedilol is a bioavailable alphaand beta-adrenoceptor blocking drug. BWA 575C [3,4] is a novel drug that combines the properties of angiotensin-converting enzyme inhibition with betaadrenoceptor blockade. Another approach has been to separate and examine the pharmacology of the individual stereoisomers of labetalol.…”
mentioning
confidence: 99%
“…This combined profile could also be demonstrated in normotensive rats and dogs as well as in conscious, renovascular hypertensive dogs [9]. The compound appears to be stable in vivo, in that it does not break down into two separate metabolites, with each containing one of the two pharmacodynamic components [8,10].…”
Section: Bevantololmentioning
confidence: 91%
“…Although the molecule contains four chiral centres, one in the side chain associated with 0adrenoceptor blocking properties and the remainder in the peptide structure associated with ACE inhibition, BW A385C is a single diastereoisomer (S,S,S,S). The pharmacological activity of the mixed isomeric form of this hybrid drug, BW A575C, has been previously described (5).…”
Section: Chemistrymentioning
confidence: 99%
“…The efficacy of ACE inhibitors in animal models of renovascular hypertension with elevated plasma renin is more established (23). Previous studies have demonstrated that BW A575C (the mixed isomeric form of BW A385C) has a potent antihypertensive action in the conscious renovascular hypertensive dog (4). In these studies, renovascular hypertension was induced by left renal artery stenosis to reduce flow by approximately 70%.…”
Section: Antihypertensive Activity In Experimental Hypertensionmentioning
confidence: 99%